Learning Through Children’s Project Work: Challenges and Dilemmas of Preschool Teachers - Stanisavljević Petrović, Zorica Č.; Manić, Iva N.; Marković, Marija R. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This study examines preschool teachers’ experiences with implementing the project-based approach in early childhood education in Serbia, with particular attention to the challenges, dilemmas, and perceived needs for professional support. Grounded in constructivist principles, project-based learning (PBL) fosters children’s curiosity, active participation, and inquiry, encouraging exploration, problem-solving, and collaboration. However, its practical application often generates uncertainties for practitioners. Although formally embedded in the national preschool curriculum framework Years of Ascent (2018), PBL in practice frequently raises questions about topic selection, sustaining children’s engagement, managing limited resources, and documenting the learning process. Employing a mixed-methods design, the study surveyed 205 preschool teachers from southern Serbia between October 2024 and April 2025 using a structured online questionnaire with both closed and open-ended questions. Quantitative findings show that 59% of teachers occasionally encounter dilemmas in planning and structuring projects, 20% face such challenges frequently, 84% report only partial confidence in their professional decisions, and 90.2% acknowledge the need for additional knowledge, training, or support. No statistically significant differences were found by years of work experience or qualification level, indicating that these challenges are consistent across professional profiles. Thematic analysis of qualitative data identified five key categories of dilemmas: topic selection and formulation; ensuring children’s sustained interest and participation; planning and implementing activities within real-world constraints; securing resources and collaborative support from colleagues, parents, and the local community; and addressing professional insecurities, particularly regarding documentation. The findings suggest that uncertainties stem largely from the inherent complexity of PBL—which requires integrating diverse pedagogical skills, adaptability, and responsiveness to dynamic classroom conditions—rather than from individual teacher characteristics. The study underscores the importance of continuous professional development, opportunities for peer learning, and stronger institutional and community partnerships. It emphasizes that both pedagogical competence and structural conditions must be strengthened to enable the confident and effective application of PBL and to fully realize its potential in supporting children’s active, meaningful, and holistic learning.